Immigrant Memoirs in the Service of Americanization: Between “the Melting Pot” and Cultural Pluralism - Anita Jarczok (European Journal of American Studies)
This article analyzes four immigrant memoirs – Mary Antin's The Promised Land (1912); Jacob Cash's What America Means to Me (1925); Constantine Panunzio's The Soul of an Immigrant (1922), and M. E. Ravage's An American in the Making (1917) – in the light of their contribution to the nationwide debate over immigration that took place against the background of heightened antagonism towards the immigrant community at the beginning of the twentieth century in the United States. It argues that these life narratives represent diverse perspectives on the Americanization process: two of them – Cash's and Antin's – seem to endorse the assimilationist point of view, while the other two – Panunzio's and Ravage's – lean more towards arguments voiced by cultural pluralists. All four texts try to refute restrictionists' claims based on pseudo-scientific racial theories. This article also suggests a way of classifying autobiographies authored by European immigrants at the turn of the twentieth century.